Improvising the integral approach model to address OSHMS leadership challenges at a Malaysian pipe coating facility - Dzulqarnain, Abu Bakar (2017)
The application of occupational safety and health management system (OSHMS) has helped industries sustain improvement in the area of safety performance. This study attempts to improvise the Integral Approach model to address OSHMS leadership challenges at a Malaysian pipe-coating facility. The basis of this study is that by improvising the application of the Integral Approach model, it can supplement the existing OSHMS by providing insight derived from the four quadrants of personal, behaviour, culture and systems. These quadrants would not be systematically evident in a traditional OSHMs certified organization as evidenced by the high numbers of accidents and incidents still occurring in the Malaysian manufacturing sector. The problem is that accidents and incidents are still occurring in organizations with established and mature OSHMS in place. This study attempts to improvise the Integral Approach model to supplement and further enhance the existing OSHMS to minimize incidents and accidents through adaptive leadership actions. This mixed method, exploratory case study applied a qualitative and quantitative data collection approach to gather data for analysis in Phase I. The data collection instrument was in the form of online survey and interviews. The qualitative data from interviews were designed to supplement the quantitative data from the online survey. The collected data was then compiled and presented as a summarized report to the Leadership Team. Following the completion of the data compilation phase, the intervention phase (Phase II) was introduced. In this phase, improvement opportunities and performance coaching to produce breakthrough results were provided. A leadership team to oversee the study activities and initiative was initiated to collaborate between the research activities and work-site activities. Various workshops and coaching session were conducted for the site leadership team members as well as key personnel. Upon completion of Phase II, the final phase of the study (Phase III) was carried out where a post survey to measure the ‘before’ and ‘after’ perception of the study initiative from the workforce was carried out. Other activities carried out in Phase III was the completion and study debrief activities for the participating organization. The results of the study indicated that there were substantial objective and subjective information that can be considered by leaders when the Integral Approach model was applied to take into account personal, behaviour, culture and systems perspective. This consideration has the potential to positively impact the safety culture and lead to positive development of the OSHMS. This study also demonstrated that the application of the Integral Approach model promoted communication and consultation between the workforce and leadership. The returned data also indicated that the workforce wanted a more integral workplace where leadership and workers were interdependent on each other. This study concludes that there is value in applying the Integral Approach model to support an existing OSHMS in identifying safety leadership actions required, and areas of safety culture improvement to be considered for action.